2018
DOI: 10.1039/c8cp01431k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the function of water during the gelation of globular proteins by temperature-dependent near infrared spectroscopy

Abstract: Water plays an indispensable role in the gelation of proteins, but its function still remains unclear. In this work, the variation of water species with the structural changes of globular proteins was investigated using temperature-dependent near infrared (NIR) spectroscopy. Ovalbumin (OVA) was used as a model protein, which forms a gel-like structure as the temperature increases through three phases, i.e., phase I (native), phase II (molten globule state), and phase III (gel state). The structural change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Similarly to perturbation by light, intentional perturbation by temperature is often used in aquaphotomics as it is possible to use temperature dependent NIR spectra to obtain structural and quantitative information of the aqueous systems [42,43,49,50]. For instance, temperature perturbation was employed to study structural changes of ovalbumin as a model protein in aqueous solutions [51]. Two-dimensional correlation NIR spectroscopy and Gaussian fitting were adopted to investigate the variation of different water species and the sequences of the changes in the structure of protein during gelation.…”
Section: Water Spectrum As a Source Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to perturbation by light, intentional perturbation by temperature is often used in aquaphotomics as it is possible to use temperature dependent NIR spectra to obtain structural and quantitative information of the aqueous systems [42,43,49,50]. For instance, temperature perturbation was employed to study structural changes of ovalbumin as a model protein in aqueous solutions [51]. Two-dimensional correlation NIR spectroscopy and Gaussian fitting were adopted to investigate the variation of different water species and the sequences of the changes in the structure of protein during gelation.…”
Section: Water Spectrum As a Source Of Informationmentioning
confidence: 99%
“…In a study of prion protein isoforms [47], aquaphotomics analysis of Mn and Cu prion isoforms in water solutions revealed that while binding of copper results in increased protein stability in water, the binding of manganese resulted in less stability—which led to fibril formation, responsible of neurodegenerative disease. The fact that the entire process of protein structural changes in aqueous systems can be monitored indirectly through the water absorbance pattern of the protein solution, was demonstrated in a study of amyloid protein—another protein involved in pathogenesis of neurodegenerative diseases [71]—as well as ovalbumin [51].…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…Structural changes during protein gelation were studied by temperature-dependent NIR spectroscopy using ovalbumin (OVA) aqueous solution. 6 The spectra of OVA solution were recorded at temperatures from 30 to 90 C with a step of 5 C. Using CWT to enhance the spectral resolution of the spectra, the peaks corresponding to a-helix and b-sheet can be identified. The opposite trend of the variation in the spectral intensity gives a clear indication for the transformation from a-helix to b-sheet.…”
Section: Development and Resultsmentioning
confidence: 99%
“…Upon heating, native globular molecules in aqueous solution unfold and expose the hydrophobic core facilitating polypeptide-polypeptide and polypeptide-water interactions [29]. This process is initiated by diminishing stability of hydrogen bonds in the hydration shell of the protein, which enables the rearrangement of chain segments to balance a multitude of attractive and repulsive forces [30]. At high enough concentrations, gels are formed upon cooling via disulfide, ionic, hydrophobic and hydrogen bonds [31].…”
Section: Effect Of Heatingmentioning
confidence: 99%